Philosophical Foundations of Education - Vinogradov, Andrey I.; Savateeva, Oxana Viktorovna; Vinogradova, Svetlana A. (Journal of History Culture and Art Research, 2020)
The article is focused on the problem of defining the philosophy of education and its subject matter. It analyses different points of view on the definition of this term and tries to combine mutually exclusive approaches. To solve this issue, the authors use the vast experience in addressing it in the late 19th and early 20th centuries in Russian and German philosophical and pedagogical thought. The authors believe that the similarity between that era and our times makes it possible to use the ideas of thinkers of the past for resolving the issues of today. Besides, the authors of the article try to define the subject matter of philosophy of education by examining the issues that can cumulatively constitute a subject of philosophy of education. They compare the terms “pedagogy” and “education” and show that shifting from one term to the other results in a loss of some meanings in an educational paradigm. They describe a specific importance of guidance in pedagogical activities. Another aspect of the subject of philosophy is the ethical nature of education. The article stresses the importance of moral development of a personality. The authors believe that it is very important to pay attention to the warning expressed by many thinkers of the late 19th and early 20th centuries on the danger of “technocratism”, i.e. prioritising technical education over humanities. Nowadays, this warning made a century ago has become even more relevant. The article further analyses the idea of correlation between guidance and politics and examines ideas of renowned thinkers on the problem of developing a free personality. Finally, the article touches upon the problem of nation-specific education. In the authors’ opinion, these issues cumulatively constitute the subject of philosophy of education.